The brush border cytoskeleton is not static: in vivo turnover of proteins (The Rockefeller University Press, 1984)
The shape and stability of intestinal epithelial cell microvilli are maintained by a cytoskeletal core composed of a bundle of actin filaments with several associated proteins. The core filaments are intimately associated with the overlying plasma membrane, in which there occur rapid turnover of proteins and constant incorporation of new membrane. Previous work has shown that starvation or inhibition of protein synthesis results in modulation of microvillar length, which indicates that there may be cytoskeletal protein turnover. We demonstrate herein, by means of in vivo pulse labeling with radioactive amino acids, that turnover of brush border cytoskeletal proteins occurs in mature absorptive cells. Turnover of cytoskeletal proteins appears to be quite slow relative to membrane protein turnover, which suggests that the turnover of these two microvillar compartments is not coupled. We thus conclude that cytoskeletal protein turnover may be a factor used to maintain normal length and stability of microvilli and that the cytoskeleton cannot be considered a static structure.